Kaji Numerik Pengaruh Eccentricity Ratio Dan Radius Bearing Terhadap Ketebalan Film Dan Tekanan Hidrodinamik Menggunakan Finite Difference Method - Arafi, Gani; Cupu, Dedi Rosa Putra; Syafri, Syafri (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Journal bearing operates, the relative motion between journal and bearing as well as lubricant form a lubricant film to prevent the direct contact between both surfaces of the journal and the bearing. The entire surface is separated by the lubricant film so that there is no direct contact between the two surfaces. This research was conducted to calculate the pressure and film thickness distribution using the Finite Difference Method (FDM) in solving partial differential equations of the Reynolds equation. The central difference scheme was used in this simulation because this scheme is more accurate than the other difference schemes. Some factors influencing the generated pressure and film thickness distribution were studied in this research, i.e. eccentricity ratio and radius of bearing. At the eccentricity ratio of 0.632 the dimensionless maximum pressure are 8.0952 which occurred at and the dimensionless minimum film thickness are 0.368 at respectively. This research also found that the greater the value of the eccentricity ratio, the greater the pressure generated between the contacting surfaces. Besides, the eccentricity ratio causing the change of the location of maximum pressure because, at axis rotation the central point of the journal and bearing center point shift with increase eccentricity ratio. Increasing of the radius bearing causes the decrease of the ratio of length and diameter of bearing (L/D ratio) and decreases the maximum pressure.Keywords: Journal bearing, Eccentricity ratio, Radius Bearing, Hydrodynamic Pressure, Film Thickness